Pengaruh Pengetahuan dan Sikap Wali Murid dan Guru Terkait Anemia pada di TK Putra I Lambheu dan TK Putra IV Ajun Kabupaten Aceh Besar Tahun 2024 - Irma Hamisah; Phossy Vionica Ramadhana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Anemia is still a public health problem in Indonesia, especially in vulnerable groups such as children and women. Knowledge and attitudes of parents and teachers play an important role in efforts to prevent anemia from an early age. Health education is a potential strategy in increasing knowledge and forming attitudes that support anemia prevention behavior. This study aims to determine the effect of health education on the level of knowledge and attitudes of parents and teachers related to anemia in Putra I Lambheu Kindergarten and Putra IV Ajun Kindergarten, Aceh Besar District. The study used a quantitative approach with a kuasi-eksperimental design. The sample amounted to 40 respondents consisting of student guardians and teachers, taken using quota sampling technique. The educational intervention was given in one session, and data were collected through pre-test and post-test questionnaires, then analyzed using the t-test. The results showed that there was a difference between knowledge before and after being given health education related to anemia (p value 0.031), while attitudes had no difference (p value 0.563). It can be concluded that health education is effective in increasing the knowledge of student guardians and teachers about anemia, but has not had a significant impact on attitude change.